Pengaruh Konsentrasi Nutrisi AB mix Terhdap Pertumbuhan dan Hasil Tanaman Seledri (Apium graveolens L.) Dengan Sistem Hidroponik NFT Effect of AB mix Nutrient Concentration on Growth and Yield of Celery (Apium graveolens L.) with NFT Hydroponic Systems - Silvani Wardi; Jeanne M. Paulus; Jemmy Najoan (Universitas Sam Ratulangi, 2019)
ABSTRACT Celery (Apium graveolens L.) is a vegetable plant that has long been known in Indonesia. Celery plants have many benefits as the food and health. The low production of quality celery and the products are produced by in accordance with the wishes of consumers. A technology is needed that can increase the production of quality celery and in accordance with the market's desires. Hydroponics film engineering technique is one of the technologies that can be applied in narrow areas, but research on the concentration of nutrients in the hydroponic planting system of celery plants has not been done much. The purpose of this study is to determine the effect of the concentration of AB mix nutrients on the growth and yield of celery plants (Apium graveolens L.) NFT hydroponic system, and get the best concentration of AB mix nutrients on the growth and yield of celery plants. This research method uses a Completely Randomized Design (CRD) with 3 treatments and 4 replications, the factors studied are the concentration of AB mix nutrition with the treatment: (p1) 900 ppm, (p2) 1200 ppm, (p3) 1500 ppm. The results showed that there was an effect of the concentration of AB mix nutrients on the growth and yield of celery (Apium graveolens L.) and the best concentration was in the treatment (p3) 1500 ppm. Keywords: Nutrient AB mix, NFT Hydroponics, Celery (Apium graveolens L.)